The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jse.12672
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic lineages and potential introgression in a mixed‐ploidy species (Phragmites australis) across temperate China

Abstract: Polyploidization and hybridization are very common in natural plant species, and mixed-ploidy species provide a unique opportunity to study the effects of evolutionary history, local abundance, and ploidy level on the direction and extent of introgression between intraspecific lineages. First, we delimited two morphologically cryptic lineages of Phragmites australis Trin. ex Steud. in temperate China using 11 nuclear microsatellites and two chloroplast DNA fragments with 225 samples from China as well as 11 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 90 publications
(130 reference statements)
2
12
1
Order By: Relevance
“…Previous studies have proposed that different ploidy levels do not cause phenotypic changes (Achenbach et al, 2012) or higher tolerance to salinity (Achenbach et al, 2013). In contrast, it has been found that octoploid P. australis were less affected by salt stress than tetraploids (Paucã-Comãnescu et al, 1999), while a recent finding showed the European lineage haplotype O (which is mainly tetraploid) was likely to be more tolerant to soil salinity than East Asian clades of haplotype P, which are more frequently octoploids (Lambertini et al, 2020;Liu et al, 2020). Ploidy has been emphasized as a key factor affecting the adaptation to new territories, for example allowing European tetraploid lineages to spread to Asian habitat (Lambertini et al, 2020), and enabling their invasion in North American environments (Pyšek et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have proposed that different ploidy levels do not cause phenotypic changes (Achenbach et al, 2012) or higher tolerance to salinity (Achenbach et al, 2013). In contrast, it has been found that octoploid P. australis were less affected by salt stress than tetraploids (Paucã-Comãnescu et al, 1999), while a recent finding showed the European lineage haplotype O (which is mainly tetraploid) was likely to be more tolerant to soil salinity than East Asian clades of haplotype P, which are more frequently octoploids (Lambertini et al, 2020;Liu et al, 2020). Ploidy has been emphasized as a key factor affecting the adaptation to new territories, for example allowing European tetraploid lineages to spread to Asian habitat (Lambertini et al, 2020), and enabling their invasion in North American environments (Pyšek et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…australis has not been investigated from a genomic perspective and lacks a reference genome that can serve as a foundational resource to investigate genomic traits underlying plant invasions and to identify genetic targets for biocontrol. Considering the diverse range of ploidy levels (Keller, 2000 ; Liu, Yin, et al, 2020 ; Pyšek et al, 2020 ) and that the genetic mechanisms and natural selection underlying diploidization of polyploids are largely unknown for angiosperms (Li et al, 2021 ), P . australis provides an ideal subject to study such evolutionary mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Although we could not obtain the sequences of trn T- trn L and rbc L– psa I regions to directly compare the results with previous studies based on chloroplast haplotypes 15,25,36 , we could infer the corresponding haplotypes by the corresponding geographic locations (Table S2). For example, the chloroplast haplotype P which is distributed in Eastern China may represent AU lineage, as they have overlapping geographic occurrences 19,37 . Each lineage was characterized by its own ploidy level: The AU is octoploid, the USland is hexaploid, and the Neoploid (South Africa) is octoploid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tetraploid and octoploid individuals are most common in nature (Connor, et al 1998;Clevering and Lissner 1999). Substantial efforts to investigate the evolution of speciation in Phragmites have been made, but the evolution of ploidy levels within this species is still unclear (Saltonstall 2002;Lambertini, et al 2006;Lambertini, Mendelssohn, et al 2012;Tanaka, et al 2017;Liu, et al 2020). To date, seven species, P. australis, P. mauritianus Kunth, P. frutescens H. Scholz, P. dioica Hackel ex Conert, P. berlandieri E.…”
Section: Introductionmentioning
confidence: 99%